Lactobacillus plantarum JCM 1149 Growth Enhancement by using Chlorella sp. KLSc61-pretreated Cells - Lalita Khanrin; Phonwimon Boonyakorn; Karn Wongsariya; Chokchai Kittiwongwattana; Cherdsak Maneeruttanarungroj; Kanogkan Leerojanaprapa; Wipawee Dejtisakdi (Journal of Pure and Applied Microbiology)
Dry microalgal biomass was previously tested as prebiotic to enhance the growth of probiotic bacteria. However, the drying process could be ineffective for scaling up probiotic production. This study aimed to investigate the use of fresh, pretreated microalgal biomass to promote the growth of Lactobacillus plantarum JCM 1149. Chlorella sp. KLSc61 cells were pretreated by three different methods: physical treatment with microwave radiation at power levels of 300, 500, and 700 W; chemical treatment with 0.1 M citric acid and 0.5 M sodium hydroxide; and biological treatment with cellulase enzyme. The 2.5% pretreated Chlorella cells were then added to L. plantarum JCM 1149 culture, and the growth was observed at 37 °C for 24 h of incubation. The results showed that, during the log phase (6-10 h), Chlorella cells pretreated with microwave radiation at 700 W were the most effective in promoting L. plantarum JCM 1149 growth, which was 1.4- and 1.5-fold of L. plantarum JCM 1149 without adding Chlorella and with untreated cells, respectively. Extension of the pretreatment time by microwave radiation at 700 W from up to 2 min increased the growth of L. plantarum JCM 1149 up to 1.8-fold of pretreatment time by microwave radiation at 700 W 1 min, compared to the control groups. Additionally, increasing the amount of Chlorella biomass up to 5% (w/v) extended the log phase of L. plantarum JCM 1149 and increased cell accumulation during the stationary phase. Unlike dry microalgal biomass, the simplicity of fresh, pretreated Chlorella biomass shown in this study may facilitate large-scale, commercial production of L. plantarum strains as probiotics.